Idiopathic esophagopathies resembling gastroesophageal reflux disease in dogs - Münster, M.; Hörauf, A.; Lübke-Becker, A.; Grest, P.; Rütten, M. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2013)
ObjectivePathologic gastroesophageal reflux (GER) has been demonstrated experimentally in dogs, and it is suspected to occur naturally in dogs, yet its clinical significance is unknown. The aim of the study was to demonstrate clinical indicators of pathologic GER in dogs with idiopathic esophagopathies. Materials and methods: Dogs with clinical signs suggestive for esophageal disease (regurgitation, ptyalism, or dysphagia) and where extraesophageal and specific esophageal diseases had been ruled out, were retrospectively diagnosed with idiopathic esophagopathies. History, physical examination findings, clinicopathologic, radiographic, and endoscopic data, and treatment results were obtained from medical records, reviewed and evaluated. Results: Out of 67 dogs with anamnestic esophageal signs, 12 (17.4%) dogs were identified as having idiopathic esophagopathies and were included in the study. Median age was 3.0 years (range 1.0–11.0), and median bodyweight was 28.2 kg (range 8.2–44.0). The most frequent anamnestic esophageal signs were ptyalism (10/12 dogs), regurgitation (8/12 dogs), signs of discomfort, pain (8/12 dogs), and cough (5/12 dogs). The most common radiographic abnormality was segmental esophageal dilation (8/12 dogs). Esophagoscopy revealed single mucosal surface defects at the gastroesophageal junction in 3/12 dogs. In dogs with altered esophageal motility, cytological and microbiological examinations of bronchial aspirates showed goblet cell hyperplasia (8/8 dogs), neutrophilic infiltration (5/8 dogs) and culturable bacteria (4/8 dogs), respectively. All dogs were treated with omeprazole (median 0.7 mg/kg once per day, range 0.5-1.2). Reported median treatment duration until remission of the main clinical signs was 20.0 days (range 8.0–54.0 days). This endpoint was reached in 11/12 dogs. Conclusion and clinical relevance: Results suggest that in some dogs with esophageal clinical signs, and where no primary disease could be identified, clinical indicators of pathologic GER such as pain, mucosal lesions and motility disturbances of the esophagus, respiratory complications, and response to therapy can be observed.
Keywords: Esophagus; endoscopy; radiology; supra-esophageal complication; canine